EFFECT OF PRE-MENSTRUAL SYNDROME (PMS) ON THE DAILY ROUTINE OF UNDERGRADUATE NURSING STUDENTS AT A PRIVATE NURSING COLLEGE, LAHORE - PATRAS, S; FIRDOS, U; MUNIR, J; WILLIAM, S; IQBAL, H; QADEER, A; ZAFAR, M (Biological and Clinical Sciences Research Journal, 2023)
Pre-menstrual Syndrome is a condition that affects women before the onset of their period, causing physical, psychological, and behavioral symptoms. Although it affects women worldwide, it primarily affects students due to their busy schedules and routines. This study aims to identify the effects of pre-menstrual Syndrome on nursing students. The objective was to examine how pre-menstrual Syndrome affects the daily routines of undergraduate nursing students. This study used a descriptive cross-sectional quantitative design, with 106 female participants selected through purposive sampling. It was conducted at a private nursing college. The results showed that the most common physiological and behavioral symptoms were lethargy, food cravings, and joint and back pain, which mainly interfered with college and daily routines. In this study, breast sensitivity affected 49% of participants, while back and joint pain affected 84.9%, and anger issues affected 55.2%. Among the participants, 26.4% had mild effects on their work or school, 34% had a moderate impact, and 12.3% had severe consequences. Participants who reported back and joint pain were 84.9%, while those who reported headaches were 75.4%, and those who experienced food cravings were 77.4%. The participants who felt anxiety were about 84.9%. The study concluded that most female nursing students suffer from pre-menstrual Syndrome every month, and it affects their college life due to the different physical and psychological symptoms it causes.